2014
DOI: 10.1186/1476-7120-12-45
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative left ventricular ejection fraction and left atrium reverse remodeling after mitral regurgitation surgery

Abstract: BackgroundLeft atrium enlargement has been associated with cardiac events in patients with mitral regurgitation (MR). Left atrium reverse remodeling (LARR) occur after surgical correction of MR, but the preoperative predictors of this phenomenon are not well known. It is therefore important to identify preoperative predictors for postoperative LARR.MethodsWe enrolled 62 patients with chronic severe MR (prolapse or flail leaflet) who underwent successful mitral valve surgery (repair or replacement); all with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
(34 reference statements)
0
8
1
1
Order By: Relevance
“…Another study suggested that MA size and reduced fractional area shortening were more related to LA rather than to LV size and dysfunction, at least in cases of degenerative severe MR with preserved LVEF 22). A decrease in LA size, or reverse remodeling, has been observed after MV surgery 10). In the present study, the LAVI obtained using echocardiography at least 6 months postoperatively was smaller in the normal annular height/BSA group than in the decreased annular height/BSA group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study suggested that MA size and reduced fractional area shortening were more related to LA rather than to LV size and dysfunction, at least in cases of degenerative severe MR with preserved LVEF 22). A decrease in LA size, or reverse remodeling, has been observed after MV surgery 10). In the present study, the LAVI obtained using echocardiography at least 6 months postoperatively was smaller in the normal annular height/BSA group than in the decreased annular height/BSA group.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, a decrease in LA size, or reverse remodeling, has been observed after MV surgery. LA reverse remodeling occur after surgery of MR with preserved LV ejection fraction (LVEF) 10). One previous study concluded that MA dysfunction might be a prognostic factor for increased repair durability and MR recurrence after successful MV repair 11).…”
Section: Introductionmentioning
confidence: 99%
“…After surgery, there was a significant reduction in the diameter of the left atrium for the majority of patients in both groups (Tables 4 and 5), regression of the size of the LA or reversibility of the remodeling, were observed after mitral valve surgery and it has been shown that the preoperative LVEF is the only variable closely associated with a postoperative reduction in LA diameter [23][24][25]. Some authors find a close association between LAD regression and reduction of cardiovascular events [11,21,23].…”
Section: Parametersmentioning
confidence: 91%
“…Some authors find a close association between LAD regression and reduction of cardiovascular events [11,21,23]. In the literature, the decline in the diameter of the LA was strongly observed after mitral surgery.…”
Section: Parametersmentioning
confidence: 97%
“…Оценка процессов ремоделирования ЛЖ включает в себя измерение линейных размеров и определение расчетных показателей [44]. Одни ученые связывают ремоделирующий процесс с гипертрофией ЛЖ, другие изучают миокардиальный стресс, фракцию выброса ЛЖ, расчетные показатели формы ЛЖ и напряжения стенок, объемные показатели [45].…”
unclassified